The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.02.28.952143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivoFeedback Control of an Antithetic Molecular-Titration Motif inEscherichia coliusing Microfluidics

Abstract: We study both in silico and in vivo the real-time feedback control of a molecular titration motif that has been earmarked as a fundamental component of antithetic and multicellular feedback control schemes in E. coli. We show that an external feedback control strategy can successfully regulate the average fluorescence output of a bacterial cell population to a desired constant level in real-time. We also provide in silico evidence that the same strategy can be used to track a time-varying reference signal wher… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Moreover, we have taken into account the following realistic constraints on the experimental platform [29] :…”
Section: Agent-based Simulations In Bsimmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we have taken into account the following realistic constraints on the experimental platform [29] :…”
Section: Agent-based Simulations In Bsimmentioning
confidence: 99%
“…Hence, when such an implementation is adopted, the control input will continue to oscillate between its possible values (Figure 3.b). As is common practice in applications where noise and uncertainties are unavoidable, a dead-zone or a delay can be added in the control loop to avoid high frequency oscillations of the control input that may cause excessive stress to cells and to the actuation system [29]. The details of the proof of convergence for the proposed relay controllers is reported in STAR Methods 7.5.…”
Section: Ratiometric Control Of Cell Populations Can Be Achieved By Using External Feedback Strategiesmentioning
confidence: 99%
“…Once trained, Cheetah segmentation masks were generated and used to calculate the number of cells and average GFP fluorescence per cell (Figures 2B, 2C). These results were compared to similar analyses using segmentation masks generated by ChipSeg that we 33,41 and others 21,22 have previously implemented in a similar experimental setup (Supplementary Movie 1; Methods). There were several clear differences between the two segmentation methods.…”
Section: Robust Image Segmentation and Analysis Of Bacteria And Mammalian Cellsmentioning
confidence: 99%
“…Results from this experiment and related replica showed that the platform was able to accurately control average mCherry fluorescence in the cells for the duration of the experiment (Figures 3C, 3D; Supplementary Figure 1; Supplementary Movie 3). To evaluate the performance of the control experiment we measured the Integral Square Error (ISE) 41 for both controlled and uncontrolled chambers (i.e. those that received the same input in open loop).…”
Section: External Feedback Control Of Protein Expression In Mammalian Cellsmentioning
confidence: 99%
“…The same core functions are implemented for both cell types, making the code flexible for other chassis and applications. The algorithm showed robust segmentation results in external feedback control experiments with microfluidics/microscopy platforms [6][7][8][9] , and can be easily adapted for open-loop experiments, other cell types and experimental settings.…”
Section: Introductionmentioning
confidence: 99%